Analisis Frekuensi dalam Penggunaan Media Sosial Berdasarkan Gender : Studi Kasus Masyarakat Buddhis di Indonesia - Wiwit Rizqiani; Nurul Hidayat (Dhammavicaya : Jurnal Pengkajian Dhamma, 2025)
This study examines the frequency and duration of accessing social media by male and female respondents of Gen Z Buddhist in Indonesia as research subjects. The method used in the study was quantitative, and the data collection technique used purposive sampling using a survey of 400 respondents aged between 17 and 28 years. Based on the results of the analysis, male respondents tend to use social media access at night, namely at 19.01 - 00.00, with an average of 3.35 with an average duration of access of 3.63, while female respondents tend to use social media access at night, namely at 19.01 - 00.00, with an average of 3.49 with an average duration of access of 3.75. In addition, of the seven social media that are often accessed by male and female respondents are Instagram and Tiktok. The type that is often accessed by respondents on social media is celebrity content. It can be concluded that female respondents tend to be more dominant in frequently accessing social media as entertainment at night after a full day of activities, apart from Gen Z as access to information for various needs such as assignments and so on.